Revitalizing Pancasila as Living Philosophy: Socratic-Based Classroom Experimentation to Foster Critical Thinking Skills - Andri Fransiskus Gultom (Actual Insight, 2025)
Traditional Pancasila education often suffers from dogmatic rote learning, distancing the state ideology from students' lived realities. This research aims to transform Pancasila from a static doctrine into a